Strategi Komunikasi Pembangunan Komunitas Sanggar Anak Sungai Deli (Sasude) Dalam Pemberdayaan Masyarakat Pinggiran Sungai Deli Kota Medan - Audina Ayu Putri; Syahrul Abidin; Rholand Muary (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to find out how the communication strategy is carried out by the Sanggar Anak Sungai Deli (Sasude) community to carry out the form of carrying out their activities so that they can be carried out properly. The development communication strategy carried out to achieve the goal of progressing the mindset of the community around the outskirts of the Deli River, Medan City in community empowerment carried out by the Deli River Child Studio Community (Sasude) in order to be able to improve the condition of the Deli riverbank and increase the mindset that is advanced and able to develop over time. time. The development communication strategy used (Sasude) is a marketing strategy, an instructional design strategy, and a participation strategy. These three things are carried out by Sasude with a fairly good strategy and design. This study uses a qualitative approach with a descriptive method. The research was conducted on the Deli Riverside, Medan City. Take 11 informants who match the predetermined criteria. The research was conducted directly in the field with predetermined informants, however, with different interview times.